VARIASI TERAPI GIGI DENGAN DIAGNOSA PULPITIS PADA PUSKESMAS DI KABUPATEN JEMBER TAHUN 2008 - Kiswaluyo Kiswaluyo (Fakultas Kesehatan Masyarakat, Universitas Jember, 2010)
Dentists were in a difficult position in reaching that aim, because oftenly dentists with all of their limitation, compulsory gave ineffective treatment. This study wanted to know the differences of teraphies of pulpitis at Public Health Center in Jember. The methode done was descriptive based on the patient`s visit data from six PHC in Jember between March – August 2008 . The Result showed that there are many various teraphies on the pulpitis . This different treatment is influenced by some factors i.e facilities and patient’s need. Keywords : Pulpitis, treatment plan